Legal mobilisation and justice: insights from the constitutional court case on international standard schools in Indonesia - Rosser, A.; Curnow, Jayne (Informa UK Limited, 2014)
Analysis of the role of courts in shaping access to justice in Indonesia has emphasised the role of judges and the incentives created for them by courts' institutional design. Alternatively, it has focused on individual justice-seekers and their capacities to choose between alternative pathways through the legal repertoire. In this paper, we suggest that ‘support structures for legal mobilisation’ (SSLMs) have also played an important role in shaping access to justice by influencing both the potential for legal mobilisation and the type of justice sought. In making this argument, we focus on a recent Constitutional Court case on ‘international standard schools’. In this case, a group of parents were able to mobilise for legal action only because NGOs provided the required technical expertise and financial resources while the central involvement of an anti-corruption NGO in the SSLM shifted the focus from parents' concerns about discrimination to corruption.